Borders of Socialism Private Spheres of Soviet Russia - Siegelbaum, L.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2006)
This fascinating book argues that in Russia the relations between culture and nation, art and life, commodity and trash, often diverged from familiar Western European or American versions of modernity. The essays show how public and private overlapped and shaped each other, creating new perspectives on individuals and society in the Soviet Union.
Keywords: Russia—History.; Europe, Eastern—History.; Russian, Soviet, and East European History